2007
DOI: 10.1002/app.26951
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite polymer electrolytes containing silica nanoparticles: Comparison between poly(ethylene glycol) and poly(ethylene oxide) dimethyl ether

Abstract: Nanocomposite polymer electrolytes consisting of low molecular weight poly(ethylene oxide) (PEO), iodine salt MI (M 5 K 1 , imidazolium 1 ), and fumed silica nanoparticles have been prepared and characterized. The effect of terminal group in PEO, i.e., hydroxyl (À ÀOH) and methyl (CH 3 ) using poly(ethylene glycol) (PEG) and PEO dimethyl ether (PEODME), respectively, was investigated on the interactions, structures, and ionic conductivities of polymer electrolytes. Wide angle X-ray scattering (WAXS), different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…These new broad absorption bands are attributed to the water molecules bound to hydrophilic polymeric chains. Different band position of -OH stretching vibrations are presumably due to the different interaction strength of water molecules with the two systems [24,25]. In the graft polymerization of POEM, two absorption bands at 1720 and 1110 cm À1 appeared, attributed to the stretching vibrations of carbonyl oxygen (C O) and ether oxygen (C-O-C), respectively [26].…”
Section: Resultsmentioning
confidence: 98%
“…These new broad absorption bands are attributed to the water molecules bound to hydrophilic polymeric chains. Different band position of -OH stretching vibrations are presumably due to the different interaction strength of water molecules with the two systems [24,25]. In the graft polymerization of POEM, two absorption bands at 1720 and 1110 cm À1 appeared, attributed to the stretching vibrations of carbonyl oxygen (C O) and ether oxygen (C-O-C), respectively [26].…”
Section: Resultsmentioning
confidence: 98%
“…The obtained values were 11.389, 11.326, 11.201, and 11.086 Å for the composites having the ZSM‐5 ratios of 5, 10, 20, and 30%, respectively. In this context, Park et al have reported a Bragg d ‐spacing decreased with increasing concentration of fumed silica nanoparticles in their polymer electrolytes/silica nano‐composites. In agreement with that work, the observed d ‐spacing decrease could be attributed to the chain contraction and/or densiffcation in composite upon the addition of ZSM‐5 zeolite.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the SiO2 nanoparticle has an amorphous phase, and it can be commercially produced as silica gel, fume-silica, and so forth. Several applications of SiO2 nanoparticles for examples such as medical purposes [22][23][24], as additives for rubber and plastics [25][26][27], as fillers for composite construction concrete [28][29][30], as stabilizers and agents drug delivery and theranostics [23,31], and as a heavy metal absorbent material in a water filter [14], [22].…”
Section: Introductionmentioning
confidence: 99%